2015
DOI: 10.1371/journal.pone.0141572
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline Protects Skeletal Muscle Cells from Cachectic Stimuli through an iNOS-Dependent Mechanism

Abstract: Dietary L-citrulline is thought to modulate muscle protein turnover by increasing L-arginine availability. To date, the direct effects of increased L-citrulline concentrations in muscle have been completely neglected. Therefore, we determined the role of L-citrulline in regulating cell size during catabolic conditions by depriving mature C2C12 myotubes of growth factors (serum free; SF) or growth factors and nutrients (HEPES buffered saline; HBS). Cells were treated with L-citrulline or equimolar concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 49 publications
3
49
0
Order By: Relevance
“…Glyine or alanine (1 g/kg) was administered ip 30 min prior to LPS administration. Based on our observations of a consistent lack of effect of L-alanine supplementation on skeletal muscle across multiple in vitro (24,26) and in vivo (6,27,28) studies, we used L-alanine as our amino acid control. Groups were matched for body mass, and food was removed 1 h before the administration of LPS (or saline in the control group).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glyine or alanine (1 g/kg) was administered ip 30 min prior to LPS administration. Based on our observations of a consistent lack of effect of L-alanine supplementation on skeletal muscle across multiple in vitro (24,26) and in vivo (6,27,28) studies, we used L-alanine as our amino acid control. Groups were matched for body mass, and food was removed 1 h before the administration of LPS (or saline in the control group).…”
Section: Animalsmentioning
confidence: 99%
“…Quantitative PCR was performed in duplicate using the Bio-Rad CFX384 PCR system (Bio-Rad Laboratories, Gladesville, New South Wales, Australia) with reaction volumes of 10 l containing Sso Advanced Universal SYBR Green Supermix (Bio-Rad Laboratories), forward and reverse primers, and cDNA template (2 ng/l). For in vivo analysis, gene expression was quantified by normalizing raw Cq values to the cDNA content of each sample and expressed as arbitrary units (AU) (26). Normalizing Cq values to cDNA content, which is not influenced by experimental intervention, is increasingly used as an alternative to reference genes such as Gapdh, ␤-actin, and 18S, which have proved unsuitable for normalization in muscle samples due to their variability under different stress conditions (e.g., exercise and denervation) (39,41,43).…”
Section: Animalsmentioning
confidence: 99%
“…We determined that T cell-intrinsic PTP(s) are critically involved in the initial upregulation of CXCR3 on T cells in ECM, and that PTP inhibition was sufficient to prevent the sequestration of pathogenic T cells within the brain. Recently, increased systemic iron levels were also shown to prevent the development of ECM by modulating the chemotactic T cell response 46 . Elevated iron levels decreased CXCR3 expression only on CD4 + T cells by interfering with IFNγ signalling 46 , in contrast to PTP inhibition, which reduced CXCR3 expression on both CD4 + and CD8 + T cells, likely through the modulation of TCR signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in porcine and human models have reported L-Cit as a potent precursor for NO synthesis (70,35,71,72), however, this is yet to be ascertained in poultry. Our study hypothesized that L-Cit, as an endogenous precursor of arginine, would modulate NO synthesis when supplemented in diets.…”
Section: Plasma Metabolites and Circulating No Levelsmentioning
confidence: 99%
“…Several studies highlight citrulline as a pharmaconutrient (28) as well as its broad therapeutic application in conditions including ischemia-reperfusion (34), muscular dysfunctions (35), metabolic syndromes (36), endothelial dysfunction (37,38), urea cycle disorders (39), cardiovascular defects (40) and renal disorders (41). Also, L-Cit has been shown to exhibit antioxidant properties (42) mostly mediated via direct reduction of hydroxyl radical formation, or indirect actions via NO synthesis (40).…”
Section: Introductionmentioning
confidence: 99%